2008
DOI: 10.1109/jlt.2008.2004720
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Optical-Filtering Enhanced Slow and Fast Light Effects in Semiconductor Optical Waveguides

Abstract: Abstract-A theoretical analysis of slow and fast light effects in semiconductor optical amplifiers based on coherent population oscillations and including the influence of optical filtering is presented. Optical filtering is shown to enable a significant increase of the controllable phase shift experienced by an intensity modulated signal traversing the waveguide. The theoretical model accounts for recent experimental results and is used to analyze and interpret the dependence on material and device parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…For many applications within microwave photonics it is rather the control of the phase shift of the microwave-modulated envelope of the optical signal that is of interest and recent progress within the field has allowed the realization of a 360 degrees phase shift at microwave frequencies of several tens of GHz [2] In this paper we review the physics of slow and fast light effects in semiconductor active waveguides [3] as well as recent progress towards the application of these effects within microwave photonics [4]. In particular, we introduce and explain the use of optical filtering [5] to increase the magnitude of the phase shift and the microwave frequency at which it can be realized. For practical applications, the signal to noise ratio is important and we discuss the tradeoffs at play here [6].…”
Section: Discussionmentioning
confidence: 99%
“…For many applications within microwave photonics it is rather the control of the phase shift of the microwave-modulated envelope of the optical signal that is of interest and recent progress within the field has allowed the realization of a 360 degrees phase shift at microwave frequencies of several tens of GHz [2] In this paper we review the physics of slow and fast light effects in semiconductor active waveguides [3] as well as recent progress towards the application of these effects within microwave photonics [4]. In particular, we introduce and explain the use of optical filtering [5] to increase the magnitude of the phase shift and the microwave frequency at which it can be realized. For practical applications, the signal to noise ratio is important and we discuss the tradeoffs at play here [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is seen from equation (55) that the group velocity v g can be essentially reduced for a large positive WG dispersion ∂n/∂k and/or material dispersion ∂n/∂ω Chang-Hasnain (2006). Such a phenomenon is called a slow light (SL) propagation Chang-Hasnain (2006), Dúill (2009), Chen (2008. The WG dispersion can be realized by using gratings, periodic resonant cavities, or photonic crystals Chang-Hasnain (2006).…”
Section: Slow Light Propagation In Soamentioning
confidence: 99%
“…Large material dispersion necessary for SL phenomenon can be obtained by using different nonlinear optical effects such as electromagnetically induced transparency, FWM, stimulated Brillouin scattering, stimulated Raman scattering, coherent population oscillations (CPO) Chang-Hasnain (2006), Dúill (2009), Chen (2008. A sinusoidally modulated pump propagating in a SOA induces XGM, XPM and FWM which results in amplitude and phase changes.…”
Section: Slow Light Propagation In Soamentioning
confidence: 99%
“…The signal velocity can be identified as the light group velocity v g for the signals used in the optical communications where the signal bandwidth (1 − 100) GHz is much less compared to the carrier frequency of about 193GHz Chang-Hasnain (2006). It is seen from equation (55) Large material dispersion necessary for SL phenomenon can be obtained by using different nonlinear optical effects such as electromagnetically induced transparency, FWM, stimulated Brillouin scattering, stimulated Raman scattering, coherent population oscillations (CPO) Chang-Hasnain (2006), Dúill (2009), Chen (2008. A sinusoidally modulated pump propagating in a SOA induces XGM, XPM and FWM which results in amplitude and phase changes.…”
Section: Slow Light Propagation In Soamentioning
confidence: 99%
“…The sinusoidal envelope of the detected total field at SOA output exhibits a nonlinear phase change that defines the slowdown factor S controllable via the SOA gain Dúill (2009). It has been experimentally demonstrated that light velocity control by CPO can be realized in bulk, QW and QD SOAs Chen (2008). The nanosecond radiative lifetime in SOAs corresponds to a GHz bandwidth and is suitable for practical applications Chang-Hasnain (2006).…”
Section: Slow Light Propagation In Soamentioning
confidence: 99%